Understanding Hadith of Imam Muslim Number 1421 According to Perspective of Informative Communication Theory - Shannon-Weaver's - Ardiansyah, M. Rafi; Andini, Musrifah Mei; Muhid (Taqaddumi: Journal of Quran and Hadith Studies, 2023)
Marriage is one of the most important basic rules of life among the general public. Marriage that is lived by humans must certainly comply with the conditions or rules that have been set and must be obeyed by humans. Before holding a contract in marriage, generally a man will make a proposal or khitbah to the woman, when the proposal process is based on the hadith narrated by Imam Muslim number 1421 the silence of a woman is considered a sign of approval which raises pros and cons, especially among women today. These problems are then analyzed with Shannon – Weaver's informative communication theory and further examined with the hermeneutic analysis tools offered by Syuhudi Ismail. The result of this study is the emergence of noise sources in the process of conveying messages to the recipient from the informant, or in this case from the man to the woman who is proposed to. As a solution to avoid this, deliberation is needed between the daughter and parents. The expected result of this deliberation is the willingness of the woman to accept as the meaning of her silence, or the rejection caused by the woman not having the courage to express it. In addition, with deliberation, it is hoped that the Shannon – Weaver informative communication model can run well so that information from the source to the recipient does not occur as a communication error that causes disruption either now or in the future.